-(7xy-10)+3(6xy+4)=

Simple and best practice solution for -(7xy-10)+3(6xy+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(7xy-10)+3(6xy+4)= equation:


Simplifying
-1(7xy + -10) + 3(6xy + 4) = 0

Reorder the terms:
-1(-10 + 7xy) + 3(6xy + 4) = 0
(-10 * -1 + 7xy * -1) + 3(6xy + 4) = 0
(10 + -7xy) + 3(6xy + 4) = 0

Reorder the terms:
10 + -7xy + 3(4 + 6xy) = 0
10 + -7xy + (4 * 3 + 6xy * 3) = 0
10 + -7xy + (12 + 18xy) = 0

Reorder the terms:
10 + 12 + -7xy + 18xy = 0

Combine like terms: 10 + 12 = 22
22 + -7xy + 18xy = 0

Combine like terms: -7xy + 18xy = 11xy
22 + 11xy = 0

Solving
22 + 11xy = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-22' to each side of the equation.
22 + -22 + 11xy = 0 + -22

Combine like terms: 22 + -22 = 0
0 + 11xy = 0 + -22
11xy = 0 + -22

Combine like terms: 0 + -22 = -22
11xy = -22

Divide each side by '11y'.
x = -2y-1

Simplifying
x = -2y-1

See similar equations:

| -9/2(x+1)=3 | | 5x+3x^2-2x^3=0 | | 3=n-(-6) | | 0.5b+4=2+3d-0.5 | | 2(-8x+5)+5x=7(x+4) | | -6x+3(3x+12)=18 | | v+(-6)=-24 | | 3x-16+3x=2+6x-18 | | .07x+.05(x-2400)=196 | | -6y-4=-5y-7 | | 2x+3(x-1)=4x-17+2x | | 12t=9(t-15) | | 10.60+106= | | r^4=1024 | | 4u^2+4u-32= | | 9=r(r-8) | | 10.60-106= | | 7-(3n-3)=2-4n | | 2(x+2)+4x=x+5 | | 7r^2-10=25 | | 7x+8=x^2 | | 9(y+9)=8y-7 | | 6b^2-11b-35=0 | | -(b+1)=10-b | | 6a+3=-3(2a-1) | | 4x-10-6x+3=5-9x-7+2x | | 1500+8x=1500+12x | | 106-21.20= | | 6p=3(t+4)-t | | 8x^2-13=-8 | | 22-(x+5)=7x-7 | | 4x-14-6x+4=6-8x-8+2x |

Equations solver categories